Link to WolframAlpha's assertion. Here's my attempt. Using the substitution $t = ax$, we can show the integral is equal to $$ \frac{1}{a} \int_0^\infty \frac{\log(t)}{1 + e^t}\, dt -\frac{\log(a)}{a} \int_0^\infty \frac{dt}{1 + e^{t} } .$$

The second integral is equal to $\log(2)$ using another substitution $v = e^t$ and partial fractions.

So I'm left with the first integral. I'll switch to complex variables for notation. I make two observations:

(I) The denominator has simple poles when $z = t = (2k-1)\cdot i \pi, \, k \in \mathbb{N}.$

(II) The numerator has a branch point $z = 0$.

  • $\begingroup$ Do you know jow to calculate $\int_0^{\infty} \frac{x^a}{e^x+1}dx$? $\endgroup$ – tired Oct 5 '16 at 9:18

Let $I$ be the integral given by

$$\bbox[5px,border:2px solid #C0A000]{I=\int_0^\infty\frac{\log(x)}{1+e^x}\,dx} \tag 1$$

Expanding the denominator of $(1)$ in a series of $e^{-nx}$ and interchanging the order of summation and integration reveals

$$\begin{align} I&=\int_0^\infty\frac{e^{-x}\log(x)}{1+e^{-x}}\,dx\\\\ &=\int_0^\infty\log(x)\sum_{n=0}^\infty (-1)^ne^{-(n+1)x}\,dx\\\\ &=\sum_{n=0}^\infty (-1)^n \int_0^\infty\log(x)e^{-(n+1)x}\,dx\\\\ &=\sum_{n=0}^\infty \frac{(-1)^n}{n+1}\int_0^\infty e^{-x}(\log(x)-\log(n+1))\,dx \\\\ &=\sum_0^\infty \frac{(-1)^{n+1}(\gamma+\log(n+1))}{n+1}\\\\ &=-\gamma\log(2)+\color{blue}{\sum_{n=1}^\infty \frac{(-1)^{n}\log(n)}{n}}\\\\ &=-\gamma\log(2)+\color{blue}{\eta'(1)}\\\\ &=-\gamma\log(2)+\gamma\log(2)-\frac12\log^2(2)\\\\ &=-\frac12\log^2(2) \end{align}$$

where $\eta'(s)$ is the derivative of the Dirichlet Eta Function with $\eta'(1)=\gamma\log(2)-\frac12\log^2(2)$ (SEE THIS ANSWER).

Therefore, we have the coveted result

$$\bbox[5px,border:2px solid #C0A000]{\int_0^\infty\frac{\log(x)}{1+e^x}\,dx=-\frac12\log^2(2)}$$

which agrees with that obtained using Wolfram Alpha!

NOTE $1$: DIRECT EVALUATION OF THE SUM $\displaystyle \sum_{n=1}^\infty \frac{(-1)^{n}\log(n)}{n}$

Here, we provide a direct evaluation of the sum $\displaystyle \sum_{n=1}^\infty \frac{(-1)^{n}\log(n)}{n}$ facilitated by use of the Euler-Maclaurin Summation Formula (EMSF). To that end we proceed.

First, we note that we can write for any $N\ge 1$

$$\begin{align} \sum_{n=1}^{2N}\frac{(-1)^{n}\log(n)}{n}&=2\sum_{n=1}^{N}\frac{\log(2n)}{2n}-\sum_{n=1}^{2N}\frac{\log(n)}{n}\\\\ &=\log(2)\sum_{n=1}^N\frac1n -\sum_{n=N+1}^{2N}\frac{\log(n)}{n} \tag 2 \end{align}$$

Using the EMSF, we expand the second sum on the right-hand side of $(2)$ to obtain

$$\begin{align} \sum_{n=N+1}^{2N}\frac{\log(n)}{n}&=\int_N^{2N}\frac{\log(x)}{x}\,dx+O\left(\frac{\log(N)}{N}\right)\\\\ &=\frac12\log^2(2N)-\frac12\log^2(N)+O\left(\frac{\log(N)}{N}\right)\\\\ &=\log(2)\log(N)+\frac12\log^2(2)+O\left(\frac{\log(N)}{N}\right) \tag 3 \end{align}$$

Substituting $(3)$ in $(2)$ reveals

$$\begin{align} \sum_{n=1}^{\infty}\frac{(-1)^{n}\log(n)}{n}&=\lim_{N\to \infty}\sum_{n=1}^{2N}\frac{(-1)^{n}\log(n)}{n}\\\\ &=\lim_{N\to \infty}\left(\log(2)\sum_{n=1}^n\frac1n -\log(2)\log(N)-\frac12\log^2(2)+O\left(\frac{\log(N)}{N}\right)\right)\\\\ &=\log(2)\lim_{N\to \infty}\left(\sum_{n=1}^N \frac1n -\log(N)\right)-\frac12\log^2(2)\\\\ &=\gamma \log(2)-\frac12\log^2(2) \end{align}$$

Therefore, we find that

$$\bbox[5px,border:2px solid #C0A000]{\sum_{n=1}^{\infty}\frac{(-1)^{n}\log(n)}{n}=\gamma \log(2)-\frac12\log^2(2)}$$

  • 1
    $\begingroup$ well done (+1)... i was looking for a more elementary way but no luck at all...:( $\endgroup$ – tired Oct 5 '16 at 19:29
  • 1
    $\begingroup$ @tired Thank you my friend! And now I am "tired." $\endgroup$ – Mark Viola Oct 5 '16 at 21:45
  • $\begingroup$ I'm so glad there's a real analysis method to the problem. Kudos! $\endgroup$ – glowsticc Oct 6 '16 at 21:49
  • $\begingroup$ @glowsticc You're quite welcome! This one was fun and it was my pleasure. -Mark $\endgroup$ – Mark Viola Oct 6 '16 at 21:52

Here is another solution, although it is not as efficient as Dr. MV's solution.

Let $$I = \int\limits_{0}^{\infty} \frac{\ln(x)}{1+e^{ax}} \mathrm{d}x$$ and \begin{align} I_{1} &= \int\limits_{0}^{\infty} \frac{x^{b}}{1+e^{ax}} \mathrm{d}x = \int\limits_{0}^{\infty} \frac{x^{b}e^{-ax}}{1+e^{-ax}} \mathrm{d}x \\ &= \sum\limits_{n=0}^{\infty} (-1)^{n} \int\limits_{0}^{\infty} x^{b} e^{-(a+na)x} \mathrm{d}x \end{align}

We designate the last integral on the right as $I_{2}$ and make the substitution $y=(a+na)x$ \begin{align} I_{2} &= \int\limits_{0}^{\infty} x^{b} e^{-(a+na)x} \mathrm{d}x \\ &= \frac{1}{(a+na)^{b+1}} \int\limits_{0}^{\infty} y^{b} e^{-y} \mathrm{d}y \\ &= \frac{\Gamma(b+1)}{(a+na)^{b+1}} \\ &= \frac{\Gamma(b+1)}{a^{b+1}} \frac{1}{(n+1)^{b+1}} \end{align}

Now $I_{1}$ becomes \begin{equation} I_{1} = \frac{\Gamma(b+1)}{a^{b+1}} \sum\limits_{n=0}^{\infty} (-1)^{n} \frac{1}{(n+1)^{b+1}} = \frac{\Gamma(b+1)}{a^{b+1}} \eta(b+1) \end{equation} and we have \begin{align} I &= \lim_{b \to 0} \frac{\partial I_{1}}{\partial b} \\ &= \lim_{b \to 0} \int\limits_{0}^{\infty} \frac{x^{b} \ln(x)}{1+e^{ax}} \mathrm{d}x \\ &= \lim_{b \to 0}\frac{\partial}{\partial b}\frac{\Gamma(b+1)\eta(b+1)}{a^{b+1}} \\ &= \lim_{b \to 0} \frac{a^{b+1} \Big[ \Gamma(b+1)\eta^{\prime}(b+1) + \Gamma^{\prime}(b+1)\eta(b+1) \Big] - \Gamma(b+1)\eta(b+1)a^{b+1}\ln(a)}{\left(a^{b+1}\right)^{2}} \\ &= \lim_{b \to 0} \frac{\Gamma(b+1)\eta^{\prime}(b+1) + \Gamma^{\prime}(b+1)\eta(b+1) - \Gamma(b+1)\eta(b+1)\ln(a)}{a^{b+1}} \\ \tag{a} &= \frac{1}{a} \left(\Big[\gamma \ln(2) - \frac{1}{2} \ln^{2}(2)\Big] -\gamma \ln(2) - \ln(2)\ln(a) \right) \\ &= -\frac{\ln(2)}{a} \left(\frac{1}{2} \ln(2) + \ln(a) \right) \end{align}

In step (a) we have \begin{align} \lim_{b \to 0} \Gamma^{\prime}(b+1)\eta(b+1) &= \lim_{b \to 0} \Gamma^(b+1)\psi(b+1)\eta(b+1) \\ &= \Gamma(1)\psi(1)\eta(1) \\ &= -\gamma \ln(2) \end{align} and \begin{align} \lim_{b \to 0} \Gamma(b+1)\eta^{\prime}(b+1) &= \lim_{s \to 1} \eta^{\prime}(s) \\ &= \lim_{s \to 1} \sum\limits_{n=0}^{\infty} (-1)^{n} \frac{\ln(n)}{n^{s}} \\ &= \gamma \ln(2) - \frac{1}{2} \ln^{2}(2) \end{align} See Dr. MV's solution for a proof of this result.


  1. $\Gamma(z)$ is the Gamma function.
  2. $\eta(s)$ is the Dirichlet eta function.
  3. $\zeta(s)$ is the Riemann zeta function.
  4. $\psi(z)$ is the digamma function.
  5. $\gamma$ is the Euler-Mascheroni constant.

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.